Importance of calving diseases and risk factors on milk production of Holsteins cows - Corassin, Carlos Humberto; Machado, Paulo Fernando; Coldebella, Arlei; Cassoli, Laerte Dagher; Soriano, Sergio (Semina: Ciências Agrárias, 2011)
This correlational study investigated the effects of the peripartum health disorders and your respective risk factors about the milk production, in the peak and to the 305 days in lactation. Holsteins cows (n = 522) of a commercial herd of the State of São Paulo, had your health and nutritional status accompanied since the beginning of the period pre-calving to the end of the lactation. Occurrence of diseases, score of body condition (at the dry off and calving), daily milk productions and milk compositions, were recorded. For statistical analysis of the data, the logistics regression and the analysis of multiple regression were used. The obtained results demonstrated that the diseases of the peripartum and your risk factors affected the milk production with different effects in function of the lactation numbers, demanding this way, larger care with the prophylactic measures to avoid the diseases, and to maximize the production of milk and the reproduction of the animals.